Diversity, Distribution, and Phenotypic Characterization of Cultivable Wild Yeasts Isolated from Natural Forest [version 3; peer review: 2 approved] - Ketema Bacha; Degife Dese; Anbessa Dabassa; Teshome Tadesse (F1000Research)
Background Yeasts are unicellular fungi that inhabit a variety of environments including plant surfaces, water, soil, and animal hosts. However, limited research has been conducted on soil and plant associated yeasts in Africa, with most studies originating from developed regions. Methods This study explored the diversity, distribution, and phenotypic characterization of cultivable wild yeast in samples from rhizosphere soil, leaves, litter, and tree bark collected from South West Ethiopia. Yeast isolates were characterized using morphological, physiological and biochemical methods, Stress-tolerant yeast species were identified using Matrix-Assisted Laser Desorption Ionization-Time of Flight (MALDI-TOF). Results Based on morphological, physiological, and biochemical analyses, a total of 15 yeast genera were identified from 23 plant species. Predominant yeast species included Candida spp., Saccharomyces spp., Meyerozyma spp., Pichia spp., Geotrichum spp., and Hanseniaspora spp. Plant species with the highest yeast diversity were Ficus vasta, Ficus exasperata, Ficus sycomorus, Cordia africana, and Ritchiea albersii. Bark samples yielded more yeast isolates than rhizosphere soil, litter, and leaves. Stress-tolerant species such as Saccharomyces cerevisiae, Candida pelliculosa, Meyerozyma guilliermondii, Pichia kluyveri, and Trichosporon asahii were identified using MALDI-TOF. Correlation analysis revealed no significant relationship between yeast populations in bark and leaf samples or between rhizosphere soil and leaves, though a weak positive correlation was found between rhizosphere soil and bark or litter. Seasonal analysis showed a strong positive correlation between yeast abundance in spring and summer, but no association between autumn and spring. Conclusion Ethiopian forests are home for various yeast species including the stress-tolerant wild yeasts. This study highlights the significant yeast diversity in Ethiopian forests, with potential applications in improving industrial fermentation processes that operate under stressful conditions.